2017
DOI: 10.1371/journal.pone.0182078
|View full text |Cite
|
Sign up to set email alerts
|

Human enteroviruses associated with and without diarrhea in Thailand between 2010 and 2016

Abstract: Non-bacterial acute gastroenteritis (AGE) associated with virus infection affects individuals living in developing countries, especially children. To investigate whether shedding of certain human enterovirus (EV) is more frequently detected in the stool of individuals with AGE of unknown etiology than individuals without AGE symptoms, we tested fecal samples collected from 2,692 individuals with diarrhea between January 2010 and December 2016. Samples were tested for rotavirus, norovirus, and EV by reverse-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…As then the NoV GII.4 is continuously circulating in this area until now. Simultaneously, the NoV studies conducted in another regions also reported the detection of NoV with the GII.4 as a common genotype detected . In the survey between 2000 and 2016, 26 different human NoV genotypes have been identified ( Figure ).…”
Section: Genotype Diversitymentioning
confidence: 80%
See 3 more Smart Citations
“…As then the NoV GII.4 is continuously circulating in this area until now. Simultaneously, the NoV studies conducted in another regions also reported the detection of NoV with the GII.4 as a common genotype detected . In the survey between 2000 and 2016, 26 different human NoV genotypes have been identified ( Figure ).…”
Section: Genotype Diversitymentioning
confidence: 80%
“…Most of epidemiological studies were conducted continuously since 2000 in Chiang Mai, northern Thailand, and some studies were performed in other regions of Thailand. The data revealed that the overall prevalence of NoV infection in patients with acute gastroenteritis in Thailand from 2000 to 2016 was 15.1% . The overall prevalence of NoV infection in different age groups (ranged from 1 day to 86 years old) showed a wide range of infection rates ranging from 0.09% to 44.7% while the prevalence of NoV infection in young children with the age of less than 5 years was found between 6.8% to 42.6%.…”
Section: Prevalence and Seasonalitymentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, the clinical importance of viruses belonging to the wide family Picornaviridae , such as enterovirus (EV), Aichi virus (AiV) and klassevirus/salivirus (KV), is up-to-date unclear, with those viruses presumably playing a rather minor epidemiological role in diarrhea [ 14 , 19 22 ]. Some subgroups of EVs have been involved as causative of at least 3.4% of AGE of unknown etiology [ 23 ]. Similarly, AiV, of the genus Kobuvirus , was initially described as cause of oyster-associated non-bacterial gastroenteritis in human [ 22 ], and later associated with AGE, reaching detection rates between 0.5 and 0.9% in Europe, and up to 4% in Asia and Africa [ 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%